Funkcja reportażu w programach telewizji regionalnej – doświadczenia i przyszłość - Sieradzka, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The author presents the achievements of interventionist journalism, based on reportage produced by regional stations of Polish National Television (TVP). The article contains three examples of topics addressed: the problems faced by a facility for handicapped children and a sport club for the unemployed, and a political conflict concerning the financing of a bridge in a small village. All of these examples demonstrate the broad thematic variety and competence of the station’s journalists – nearly all of their interventions were effective.